The Role of The Tense Category in The Linguistic Imagery of The World (Eurasian Journal of Learning and Academic Teaching, 2023)
In this article, it is explained that the method of semantic-structural-typological analysis of the elements of the tense paradigm has been developed. The elements of the national linguistic image of the world in English and Uzbek are studied linguotypologically. The materials collected in the course of the research pave the way to determine the integration, syntactic function and semantic possibilities of the elements of the time paradigm in English and Uzbek. Traditional Uzbek and English linguistics limit the study of the meaning of time within the morphological category of the same name. It is said that the meaning of time is not limited only to this morphological category.